2014
DOI: 10.1002/mats.201300141
|View full text |Cite
|
Sign up to set email alerts
|

At the Limits of Simulation: A New Method to Predict Thermal Degradation Behavior in Cyanate Esters and Nanocomposites Using Molecular Dynamics Simulation

Abstract: Despite their inability to model bond breaking molecular dynamics simulations are shown to predict thermal degradation temperatures of polycyanurate (cyanate ester) homopolymers and nanocomposites in very close agreement with experimental data. Simulated polymer density, used to predict Tg also shows a reduction within the same temperature range as experimental values for the thermal degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Temperature ramped molecular dynamics simulation was also employed to probe the onset of thermal degradation (T d )the latter is a comparatively recent. 23 addition to our panoply of simulation techniques and has been employed with some success to examine the degradation behaviour of thermosetting polymers such as cyanate esters, 24 polybenzoxazines, 25 and epoxy resins. 26 TGA revealed that T d was found empirically to be relatively insensitive to incorporation of POSS at this level and this again borne out by the simulations, which indicates that there are no interactions taking place in the nanocomposites that are not accounted for in the model.…”
Section: Examination Of the Inuence Of Nanollers On The Thermal And...mentioning
confidence: 99%
“…Temperature ramped molecular dynamics simulation was also employed to probe the onset of thermal degradation (T d )the latter is a comparatively recent. 23 addition to our panoply of simulation techniques and has been employed with some success to examine the degradation behaviour of thermosetting polymers such as cyanate esters, 24 polybenzoxazines, 25 and epoxy resins. 26 TGA revealed that T d was found empirically to be relatively insensitive to incorporation of POSS at this level and this again borne out by the simulations, which indicates that there are no interactions taking place in the nanocomposites that are not accounted for in the model.…”
Section: Examination Of the Inuence Of Nanollers On The Thermal And...mentioning
confidence: 99%
“…The polymers could be divided into three classes by their aging rates as fast, medium, and slow ones. Howlin et al have employed molecular dynamics to predict the onset of thermal aging for thermosetting polymers, and the results could be verified by thermogravimetric analysis . Narasimhan has investigated the heterogeneous erosion for biodegradable polymers at a molecular level .…”
Section: Other Strategies Of Lifecycle Analysis For Polymersmentioning
confidence: 99%
“…Howlin et al have employed molecular dynamics to predict the onset of thermal aging for thermosetting polymers, and the results could be verified by thermogravimetric analysis. 424 Narasimhan has investigated the heterogeneous erosion for biodegradable polymers at a molecular level. 425 Lendlein and co-workers have studied bond cleavage statistics by Monte Carlo simulations, as a derivation of the random chain cut mechanism.…”
Section: Simulation Strategies To Study Polymer Aging Evolutionmentioning
confidence: 99%